1866 Miss. Laws 82-86, 91, 165 - (:unkn) unknown (My University, 1865)
Prohibited any "freedman, free negro or mulatto" from keeping or carrying any firearms, ammunition, dirk, or bowie knife.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES